Enhanced pilot bioremediation of oily sludge from petroleum refinery disposal under hot-summer Mediterranean climate - Said, Olfa Ben; Cravo-Laureau, Cristiana; Armougom, Fabrice; Cipullo, Sabrina; Khelil, Meriem Ben; Yahiya, Marouen Ben Haj; Douihech, Abdeljabar; Beyrem, Hamouda; Coulon, Frederic; Duran, Robert (Elsevier, 2021)
Large pilot scale bioremediation approaches were implemented for the treatments of oily sludge (OS) characterised by alkaline pH (pH > 9), high concentration of metals (3% dry weight) and high total petroleum hydrocarbons content (TPH) rangingbetween 22,000 and 67,300 mg kg −1 from a Tunisian petroleum refinery. The treatments included bioaugmentation and biostimulation approaches with autochthonous isolated bacterial strains and consortia. Chemical, microbial, and ecotoxicological analyses were performed over a period of 180 days incubation. The bioremediation treatments favoured the development of Proteobacteria, Firmicutes and Bacteroidetes following an ecological succession of specialist bacterial groups, first associated to hydrocarbon degradation (e.g. Marinobacter and Alcanivorax) that resulted in a greater extent of TPH-degradation (up to 80%), and the selection of metal resistant bacteria including Hyphomonas, Phaeobacter, and Desulfuromusa. The best performances were obtained when bioaugmentation and biostimulation were combined. Over 90% of the TPH initial concentration was degraded over 180 days, which was accompanied with a 3-fold reduction of ecotoxicity. Our study demonstrates the efficacy of large pilot scale bioremediation of highly contaminated oily sludge, providing the evidence that the management of autochthonous microbial communities is of paramount importance for the success of the bioremediation process.
Keywords: Bacterial consortium; Illumina sequencing; Metal; Hydrocarbons; Ecotoxicity; Ecological succession